2014
DOI: 10.1021/mp500508w
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Specific Formation of d-Amino Acids in a Monoclonal Antibody during Light Exposure

Abstract: The photoirradiation of a monoclonal antibody 1 (mAb1) at λ = 254 nm and λmax = 305 nm resulted in the sequence-specific generation of d-Val, d-Tyr, and potentially d-Ala and d-Arg, in the heavy chain sequence [95-101] YCARVVY. d-Amino acid formation is most likely the product of reversible intermediary carbon-centered radical formation at the (α)C-positions of the respective amino acids ((α)C(•) radicals) through the action of Cys thiyl radicals (CysS(•)). The latter can be generated photochemically either th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…In fact, D-alanine formation was detected in model peptides [60], and during light-induced thiyl radical generation in IgG1[88]. These observations are consistent with synthetic applications, where thiyl radicals where used for the racemization of amines [89].…”
Section: Hydrogen Transfer Reactions Of Thiyl Radicalssupporting
confidence: 54%
“…In fact, D-alanine formation was detected in model peptides [60], and during light-induced thiyl radical generation in IgG1[88]. These observations are consistent with synthetic applications, where thiyl radicals where used for the racemization of amines [89].…”
Section: Hydrogen Transfer Reactions Of Thiyl Radicalssupporting
confidence: 54%
“…However, this does not imply quantitative repair . Our model suggests the formation of additional products, mainly protein aldehydes from the hydrolysis of thioaldehydes and protein-bound D-cysteine (or other D-amino acids[51]). Such species would not be found in standard assays.…”
Section: Discussionmentioning
confidence: 99%
“…While thiyl radicals were not generated through physiological processes in these studies, they are relevant to physiology as they demonstrate what can happen when thiyl radicals are generated on proteins. In the absence of oxygen, the reversible generation of carbon-centered radicals has led to the conversion of L-Ala to D-Ala in a model peptide[32], and to the sequence-specific generation of D-amino acids on IgG1[51]. Hence, thiyl radical generation on proteins is a viable source for D-amino acid generation, and such reactions have to be taken into account when simulating thiyl radical reaction pathways in proteins (see below).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the sequence-specific generation of D-Val, D-Tyr, and potentially D-Ala and D-Arg was proposed. 21 Recent research also demonstrated that exposing mAbs to light during their production process clearly alters the charge variants profile of the final product. 22 There is therefore extensive evidence that photodegradation leads primarily to chemical changes in single amino acids of proteins and that trp, tyr, phe, and cys are the primary targets of photodegradation.…”
Section: Introductionmentioning
confidence: 99%